Adsorption of anions on bismuth and cadmium single crystal plane electrodes from various solvents and ionic liquid mixtures. (1st October 2019) - Oll, Ove; Väärtnõu, Mart; Gorbatovski, Georg; Zhao, Jinfeng; Siimenson, Carolin; Siinor, Liis; Lust, Karmen; Romann, Tavo; Pikma, Piret; Lust, Enn
Abstract: Electrical double layer characteristics and specific adsorption of anions at Bi and Cd single crystal planes from aprotic and other non-aqueous electrolytes, as well as mixtures of surface-inactive and surface-active ionic liquids have been studied and analysed. Strong influence of sp-metal electronic characteristics (concentration of charge carriers, effective mass of electrons) on the potential of zero charge and differential capacitance values have been demonstrated. Influence of solvent chemical composition and dielectric characteristics on the surface activity and Gibbs adsorption energy values of anions at sp-metal single crystal planes has been demonstrated. Influence of ionic liquid anion composition on the specific adsorption characteristic time constant at Bi( hkl ) and Cd(0001) single crystal electrodes in comparison with aprotic and non-aqueous solvent based electrolytes demonstrates the role of the solvent properties on the adsorption process characteristics. The non-aqueous solvent (acetonitrile, ethylene carbonate, propylene carbonate and gamma-butyrolactone) based electrolytes, ionic liquids and ionic liquid mixtures discussed are important electrolytes applicable in electrical double layer capacitors, secondary-ion batteries and other electrochemical devices. Appreciable increase of specific energy and power densities has been demonstrated for supercapacitors with ionic liquid electrolytes containing iodide and bromide anions, development of which was based on the adsorption data collected and discussed. Graphical abstract: Image 1035 Highlights: Comprehensive analysis of halide ion adsorption at sp-metal interfaces is given. C vs. E curves are characteristically affected by sp-metal crystallographic orientation. Similarities between ionic liquid, aqueous and organic electrolytes are demonstrated. Significant differences in adsorption activity and anion structure are revealed.